Advances in digital technologies proceedings of the 7th International Conference on Applications of Digital Information and Web Technologies 2016 - Mizera-Petraszko, Jolanta; Chung, Yao-Liang; Pichappan, Pit (Frontiers in artificial intelligence and applications ;, 2016)
This book is aimed at building the infrastructure necessary for the large-scale development of web technologies, and attracts participants from many countries who attend the conference to demonstrate and discuss their research findings.